2023
DOI: 10.3389/fnmol.2022.1091402
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism and effect of repetitive transcranial magnetic stimulation for post-stroke pain

Abstract: Post-stroke pain (PSP) is a common complication after stroke and affects patients' quality of life. Currently, drug therapy and non-invasive brain stimulation are common treatments for PSP. Given the poor efficacy of drug therapy and various side effects, non-invasive brain stimulation, such as repetitive transcranial magnetic stimulation (rTMS), has been accepted by many patients and attracted the attention of many researchers because of its non-invasive and painless nature. This article reviews the therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 71 publications
0
26
0
Order By: Relevance
“…Although non-invasive brain stimulation appears to be effective for the treatment of fibromyalgia, rTMS and tDCS effects might not be specific to the symptoms of this pathology. Thus, rTMS protocols described in clinical fibromyalgia studies have shown similar effectiveness for relieving rheumatic [ 101 , 102 ] and post-stroke [ 103 ] pain. Likewise, the therapeutic effects of electric brain stimulation also do not seem to be restricted to fibromyalgia, as pain improvements after tDCS interventions have been described in patients with different pain syndromes (trigeminal neuralgia, poststroke pain syndrome, back pain, and fibromyalgia) [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although non-invasive brain stimulation appears to be effective for the treatment of fibromyalgia, rTMS and tDCS effects might not be specific to the symptoms of this pathology. Thus, rTMS protocols described in clinical fibromyalgia studies have shown similar effectiveness for relieving rheumatic [ 101 , 102 ] and post-stroke [ 103 ] pain. Likewise, the therapeutic effects of electric brain stimulation also do not seem to be restricted to fibromyalgia, as pain improvements after tDCS interventions have been described in patients with different pain syndromes (trigeminal neuralgia, poststroke pain syndrome, back pain, and fibromyalgia) [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 showed the results of the risk-of-bias evaluations. Randomized grouping was judged to be "high risk" because odd and even numbers were used in one study, 50 and 35 studies [14][15][16][18][19][20][21][22][23][24][25][26]29,30,32,33,[35][36][37][38]41,42,[44][45][46]48,49,52,57,59,60,64,66,68,69 were judged as "low risk." Regarding allocation concealment, three studies 29,37,59 that reported the allocation concealment method were judged as "low risk."…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Of these 61 studies, a total of 28 studies 14,[18][19][20][21][23][24][25][30][31][32]34,35,37,[39][40][41]47,49,51,52,54,57,59,66,69,73,74 used a frequency of 10 Hz for HF-rTMS, 13 studies 15,22,26,29,33,38,44,45,61,65,67,68,71 used 5 Hz, and the others used 2-50 Hz. The resting motor threshold (MT) is the minimum intensity of TMS stimulation of a fully relaxed muscle that elicits an electromyograph response of at least 50 μV with a probability of 50%.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations